Audio Describing Football: A Case Study of Bohemians FC - Moorkens, Joss; Pintado Gutiérrez, Lucía (The Journal of Specialised Translation, 2026)
As organisers of popular public events, football clubs are increasingly expected to foreground accessibility. This has led many European clubs to provide audio-described commentary (ADC) in their stadiums so that spectators who are blind and partially sighted can enjoy the matchday experience. ADC differs from regular football commentary by describing action rather than just commenting on it. At small clubs, ADC provision is usually delivered by volunteers, as is the case at Dublin club Bohemians FC, which has provided in-stadium ADC since 2019, resulting in a Total Access award from CAFE (Centre for Access to Football in Europe) in 2022. Using interviews with club staff, AD commentators and ADC users, this article documents the development of ADC provision at Bohemians as part of the club’s societal mission. This study covers commentator training, general guidelines, and the perceptions of ADC providers and users. ADC was the gateway to accessibility for most commentators, who have a personal interest in accessibility and are fans of the club. For some users, the provision of ADC has been transformative, but take-up overall has been low. Nonetheless, the service has proved impactful for football in Ireland, leading several other clubs to offer ADC.